Pyrene biodegradation and proteomic analysis in Achromobacter xylosoxidans, PY4 strain. (May 2018) - Nzila, Alexis; Ramirez, Camila Ortega; Musa, Musa M.; Sankara, Saravanan; Basheer, Chanbasha; Li, Qing X.
Abstract: Polycyclic aromatic hydrocarbons (PAHs) are environmental pollutants from incomplete combustion and petroleum products. As the molecular weight increases, PAHs become more recalcitrant to biodegradation. A bacterial strain capable of metabolizing the four fused aromatic ring PAH pyrene was isolated and characterized. The analysis of 16S rRNA gene revealed that it belongs to Achromobacter xylosoxidans species . A. xylosoxidans PY4 can utilize pyrene as the sole source of carbon. PY4 has a doubling time (dt) of less than 1 day when it grows in the presence of 1–5 mg l −1 pyrene, a dt range similar to that of the most efficient pyrene biodegrading bacteria described so far. The optimal pyrene degradation conditions are at pH 7–9, 37–40 °C, and 0–2.5% NaCl. PY4 also utilizes salicylic acid, catechol, naphthalene, anthracene and phenanthrene. PY4 degrades more than 50% of 100 mg l −1 of pyrene, within the first 15 days, at a rate of 0.069 day −1, R 2 = 0.99. The metabolites include monohydroxypyrene, 1-methoxyl-2-H-benzo[h]chromene-2-carboxylic acid, 9, 10-phenanthrenequinone, 1-methoxyl-trans-2′-carboxybenzalpyruvate, and dibutyl-phthalate. Up-expressed proteins in response to pyrene are involved in cell homeostasis, genetic information synthesis and storage, and chemical stress. Among these proteins are 4-hydroxyphenylpyruvate dioxygenase and homogentisate 1, 2-dioxygenase, involved in the lower pyrene degradation pathway. Highlights: An Achromobacter xylosoxidans PY4 strain degrading pyrene was isolated. This strain has a doubling time <1 day in the presence of 1–5 mg l −1 pyrene. Aromatic compounds of smaller molecular weight than pyrene are also utilised efficiently by this strain. Within 15 days of culture, the strain can utilise more than 50% of 100 mg l −1 of pyrene. Key enzymes involved in pyrene degradation and a biochemical pathway of this degradation has been proposed.